Rational Design of Soft–Hard Interfaces through Bioinspired Engineering. Issue 1 (13th October 2022) - Zhang, Hui; Ma, Yufei; Wang, Yijie; Niu, Lin; Zou, Rui; Zhang, Min; Liu, Hao; Genin, Guy M.; Li, Ang; Xu, Feng
Abstract: Soft–hard tissue interfaces in nature present a diversity of hierarchical transitions in composition and structure to address the challenge of stress concentrations that would otherwise arise at their interface. The translation of these into engineered materials holds promise for improved function of biomedical interfaces. Here, soft–hard tissue interfaces found in the body in health and disease, and the application of the diverse, functionally graded, and hierarchical structures that they present to bioinspired engineering materials are reviewed. A range of such bioinspired engineering materials and associated manufacturing technologies that are on the horizon in interfacial tissue engineering, hydrogel bioadhesion at the interfaces, and healthcare and medical devices are described. Abstract : Soft–hard tissue interfaces present the design motifs with hierarchical structures and gradients. Translation of the design motifs to bioinspired engineering materials including interfacial tissue engineering, hydrogel bioadhesion at the interfaces, and healthcare and medical devices may pave the way to improved repair of injured tissue in vivo and speed the development of engineered solutions to materials' interface problems.